Erosive effect of beverages on surface hardness and ultra-structure of deciduous teeth enamel. Issue 3 (December 2022) - Arafa, Abla; Filfilan, Sahab Salah; Fansa, Hoda A.
Abstract: Objectives: To assess the erosive potential of commonly used beverages on the surface micro-hardness and ultra-structure of deciduous teeth enamel. Materials and methods: A total of 52 human extracted deciduous molars were subjected to erosive challenge by cyclic immersion in four beverages: G1: artificial saliva, G2: strawberry-flavored milk, G3: orange juice, and G4: carbonated drink-Pepsi, for a 28- day pH cycling protocol. The enamel surface micro-hardness (SMH), and surface topography using a scanning electron microscope (SEM) were assessed at baseline, after two- and four-weeks of the erosive challenge. The SMH findings were statistically analyzed using the SPSS program at p ≤ 0.05 significance. Results: The pH of G4 and G3 showed significantly highly acidic pH. Both G4 and G3 showed the lowest SMH by four-week erosive challenge. By two-week erosive challenge, groups were ranked according to SMH as follows; G4 <G3 <G2 <G1. However, SMH of both G4 and G3 yielded significantly lower values compared to G2 and G1 by four weeks. The SEM of G4 and G3 depicted advanced alteration of surface enamel with increased erosive challenge exposure time. Conclusion: Carbonated soft drink (Pepsi) and orange juice showed high erosive potentiality affecting the enamel surface of deciduous teeth while milk-based beverage showed no difference from the artificial saliva.